Application of nanoparticles in antibody drug delivery - Xiefukaiti, Wumiti; Zhu, Qingmei; Dolkun, Nadira; Xiao, XueJun (Frontiers in Bioengineering and Biotechnology, 2026)
Due to their special molecular weight and pharmacokinetic/pharmacodynamic (PK/PD) characteristics, antibody drugs have difficulty crossing the body barrier and entering complex microenvironments to provide effective treatment for encephalopathy, cancer, and severe infectious diseases. With the development and application of nanotechnology, drugs can be modified by nanomethods to increase the delivery efficiency, targeting, and permeability, reduce the resistance to the antibody, and improve the response rate, thus increasing their safety and effectiveness. Therefore, nanoparticles have extensive research and application value in drug delivery systems. This article summarizes the characteristics of nanoparticles and nanoantibody delivery systems to provide a reference for the future application of nanoparticles in drug delivery.